Electromagnetic Fields and Waves - Ho Yeap, Kim; Hirasawa, Kazuhiro (IntechOpen, 2019)
In this book, a variety of topics related to electromagnetic fields and waves are extensively discussed. The topics encompass the physics of electromagnetic waves, their interactions with different kinds of media, and their applications and effects.